2022
DOI: 10.1128/spectrum.01331-22
|View full text |Cite
|
Sign up to set email alerts
|

Desaturation of the Sphingofungin Polyketide Tail Results in Increased Serine Palmitoyltransferase Inhibition

Abstract: Targeting the cellular sphingolipid metabolism is often discussed as a potential approach to treat associated human diseases such as cancer and Alzheimer's disease. Alternatively, it is also a possible target for the development of antifungal compounds, which are direly needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…To ensure the required palmitoyl-CoA for the reaction, we supplied palmitic acid to the reaction mix and additionally incubated the purified Escherichia coli -derived fatty-acid-CoA ligase FadD, together with SphA ( 34 ). Although the production of 3-ketodihydrosphinganine was lower compared to the SPT positive control [isolated from Sphingomonas paucimobilis ( 19 )], we confirmed that SphA has SPT activity and that its dual functionality is driven by the availability of the used substrates ( Fig. 4A ).…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…To ensure the required palmitoyl-CoA for the reaction, we supplied palmitic acid to the reaction mix and additionally incubated the purified Escherichia coli -derived fatty-acid-CoA ligase FadD, together with SphA ( 34 ). Although the production of 3-ketodihydrosphinganine was lower compared to the SPT positive control [isolated from Sphingomonas paucimobilis ( 19 )], we confirmed that SphA has SPT activity and that its dual functionality is driven by the availability of the used substrates ( Fig. 4A ).…”
Section: Resultssupporting
confidence: 67%
“…Analysis of the SphA activity was done with previously purified FadD, SphA, and SPT enzymes and already described protocol ( 18 , 19 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphingofungin is a polyketide-derived compound, which was first isolated from A. fumigatus in 1992 [108]. Sphingofungin is known to inhibit serine palmitoyl transferase (SPT) [109], which plays a crucial role in the biosynthesis of sphingolipids (SLs) [110]. Recently, using confocal microscopy, it was shown that the synthesis of sphingofungins and SLs was partially co-compartmentalized in the ER and ER-derived vesicles [111].…”
Section: Timeline Of Linkage Of Natural Products To Specific Bgcsmentioning
confidence: 99%
“…For example, motif 1 was the only one present in CarAGT2, Aminotransferases and other enzymes display some structural domains that are highly conserved throughout evolution. Aminotran_5 (PF00266), which encodes a protein that is a phosphoserine aminotransferase, regulates immune function and is involved in oxidative stress [29] including CarSPTa, CarSPTb, and CarKBL. Transmembrane domains may function as membrane receptors, membrane-anchored proteins, or ion channel proteins localized on the membrane [30,31].…”
Section: Discussionmentioning
confidence: 99%